Interface Issues and Challenges in All‐Solid‐State Batteries: Lithium, Sodium, and Beyond - Lou, Shuaifeng; Zhang, Fang; Fu, Chuankai; Chen, Ming; Ma, Yulin; Yin, Geping; Wang, Jiajun (Advanced materials (Weinheim), 2021)
Owing to the promise of high safety and energy density, all‐solid‐state batteries are attracting incremental interest as one of the most promising next‐generation energy storage systems. However, their widespread applications are inhibited by many technical challenges, including low‐conductivity electrolytes, dendrite growth, and poor cycle/rate properties. Particularly, the interfacial dynamics between the solid electrolyte and the electrode is considered as a crucial factor in determining solid‐state battery performance. In recent years, intensive research efforts have been devoted to understanding the interfacial behavior and strategies to overcome these challenges for all‐solid‐state batteries. Here, the interfacial principle and engineering in a variety of solid‐state batteries, including solid‐state lithium/sodium batteries and emerging batteries (lithium–sulfur, lithium–air, etc.), are discussed. Specific attention is paid to interface physics (contact and wettability) and interface chemistry (passivation layer, ionic transport, dendrite growth), as well as the strategies to address the above concerns. The purpose here is to outline the current interface issues and challenges, allowing for target‐oriented research for solid‐state electrochemical energy storage. Current trends and future perspectives in interfacial engineering are also presented. The interfacial dynamics between solid electrolytes and electrodes are considered as a crucial factor in determining all‐solid‐state battery performance. The interfacial principle and engineering in a variety of solid‐state batteries, including solid‐state lithium/sodium batteries and emerging batteries, are discussed. Specifc attention is paid to interface physics and interface chemistry, as well as the strategies to address the above concerns.